The chemist's companion : a handbook of practical data, techniques, and references - Gordon, Arnold Jacob, 1937-; Ford, Richard Alan, 1940- (New York (N.Y.) : Wiley, 1972)
The Chemist's Companion A Handbook of Practical Data, Techniques, and References Arnold J. Gordon and Richard A. Ford Contents Properties of Molecular Systems Properties of Solvents and Common Liquids ; Azeotropic Data ; Empirical Boiling Point-Pressure Relationships ; Properties of Selected Gases ; Properties of Representative Fused Salt Systems ; Structure and Properties of Naturally Occurring [alpha]-Amino Acids ; Properties and Applications of Liquid Crystals ; Prototropic Tautomerism ; Acids and Bases ; Properties of Atoms and Bonds Properties of the Elements ; Table of Isotopes ; Selected Bond Lengths ; Effective van der Waals Radii ; Bond Angles and Hybridization ; Selected Bond Strengths ; Force Constants ; Torsion and Inversion Barriers ; Bond and Group Dipole Moments ; Aromaticity ; Kinetics and Energetics Activation Parameters and Kinetics of Selected Reactions ; Linear Free Energy Relationships ; Conformational Free Energy Values ; Free Energy-Composition Chart ; Spectroscopy The Electromagnetic Spectrum ; Solvents and Other Media for Spectral Measurements ; Optical Materials for Spectroscopy and Photochemistry ; Vibration Spectra ; Electronic Absorption and Emission Spectra: Uv and Vis ; Optical Activity and Optical Rotation ; Mass Spectrometry ; Nuclear Magnetic Resonance Spectroscopy ; Electron Spin Resonance Spectroscopy ; Nuclear Quadrupole Resonance Spectroscopy ; Bibliography of Spectral Data Compilations ; Photochemistry Electronic Energy State Diagram ; Excited State Energy Transfer: Sensitizers and Quenchers ; Photochemistry Light Sources and Equipment ; Chemical Actinometry: Quantum Yield ; Suppliers ; References ; Chromatography Fundamental Types of Chromatography and Basic Definitions ; Adsorption Chromatography ; Paper Chromatography
Includes bibliographical references.
Keywords: Chemical industry; Chemie -- Encyclopedieën; Chemistry -- Handbooks, manuals, etc; Chemistry